Additional Punishment for Revocation of Political Rights to Corruption Prisoners in The Purpose of Punishment In Indonesia - Sutrisno, Sutrisno; Haryadi, Dwi; Manik, Jean Darc Noviayanti (Universitas Negeri Semarang (UNNES), 2020)
The application of additional punishment of the revocation of political rights in the form of voting and/or voting rights elected in the elections to the corruption convicts was as an attempt to eradicate the extraordinary Corruption of crime and part of severe punishment and a charge of corruption convicts. The purpose of this research, namely: first, to know and analyze the implementation requirements of additional punishment of revocation of political rights to corruption prisoners in the perspective of human rights; Second, to know and analyze the position of additional penalty for the revocation of political rights in the purpose of punishment in Indonesia. The type of research used is normative juridical research with a legal approach, conceptual approach, a case approach approach, and a comparative approach. The results of the study proved that: first, political rights can be classified in the right to freedom of thought and a conscience that is unable to be reduced under any circumstance and attached to the status of citizens. The application of the additional penalty was the act of degrading and dignity of corruption prisoners as citizens because of the impact on the elimination of Rights and the disclosure of political rights of corruption prisoners until its application does not meet the requirements of the restriction on human rights in the perspective of the relative-particulate matter; Secondly, the theory of the goal of punishment in accordance with Indonesian philosophy is correctional which is also a rationality of the implementation of prison sentence as does Law No. 12 of 1995 about Correctional. The position of additional penalty for revocation of political rights is as an instrument of conforming or contrary to the purpose of punishment in Indonesia, namely correctional throughout its application to open an opportunity for the elimination of rights and not accompanied by an attempt to recover the rights that have been revoked